Primary care and cancer: Facing the challenge of early diagnosis and survivorship. (17th May 2017) - Round, Thomas
Abstract : With ageing populations and an increasing lifetime risk of cancer, primary care will continue to play an increasingly important role in early diagnosis and cancer survivorship, especially with the lowering of risk thresholds for referral and diagnostic investigations. However, primary care in many countries is in crisis with increasing workloads for primary care physicians. Potential solutions to these challenges will be outlined including development of multidisciplinary teams, diagnostic decision support, increasing access to diagnostics and cost‐effective referral pathways.